Peristaltic flow and heat transfer of a conducting Phan-Thien-Tanner fluid in an asymmetric channel - application to chyme movement in small intestine - Vajravelu, Kuppalapalle; Sreenadh, S.; Dhananjaya, S.; Lakshminarayana, Pallavarapu (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, the influence of heat transfer on the peristaltic flow of a conducting Phan-Thien-Tanner fluid in an asymmetric channel with porous medium is studied. The coupled nonlinear governing differential equations are solved by a perturbation technique. The expressions for the temperature field, the stream function, the axial velocity, and the pressure gradient are obtained. The effects of the various physical parameters on the pumping phenomenon are analyzed through graphs and the results are discussed in detail. It is observed that the velocity and the pressure are decreased with increasing the magnetic parameter M whereas the effect of the parameter M on the temperature field is quite the opposite.
Keywords: peristaltic flow; Phan-Thien-Tanner fluid; asymmetric channel; porous medium; trapping phenomena